Measuring plasma-generated ·OH and O atoms in liquid using EPR spectroscopy and the non-selectivity of the HTA assay. (26th January 2021) - Myers, B; Ranieri, P; Smirnova, T; Hewitt, P; Peterson, D; Herrera Quesada, M; Lenker, E; Stapelmann, K
Abstract: Plasma-generated hydroxyl radicals ( · OH) and oxygen atoms (O) produced by the COST reference plasma jet, a micro-scaled atmospheric pressure plasma jet, were investigated using a variety of experimental techniques. Several gas admixtures were studied to distinguish the contributions of the two reactive oxygen species. Large discrepancies between inferred aqueous · OH densities were noted when using a 2-hydroxyterephthalic acid (HTA) fluorescence assay and electron paramagnetic resonance (EPR) measurements with the spin trap 5, 5-dimethyl-1-pyrroline N -oxide—especially when oxygen was present in the feed gas. A series of follow-up experiments including optical emission spectroscopy, H2 O2 quantification, and EPR measurements of atomic oxygen using the spin trap 2, 2, 6, 6-tetramethylpiperidine, revealed that the inconsistencies between the measured aqueous · OH were likely due to the propensity of atomic oxygen to hydroxylate TA in a manner indistinguishable from · OH. This renders the HTA assay non-selective when both · OH radicals and atomic oxygen are present, which we report for all three gas admixtures in our experiments. Additionally, considerable degradation of both HTA and the spin adducts measured using EPR spectroscopy was apparent, meaning actual radical densities in the plasma-treated liquid may be considerably higher than implied. Degradation rates compared favorably to previously measured gas phase densities of atomic oxygen in the predecessor of the COST jet and reported degradation of other chemical probes. These results show the prolific role of atomic oxygen in plasma-induced liquid chemistry and caution against diagnostic techniques that are unable to account for it.